Brain-derived neuerotrophic factor and related mechanisms that mediate and influence progesterone-induced neuroprotection - Singh, Meharvan; Krishnamoorthy, Vignesh R.; Kim, Seongcheol; Khurana, Saira; LaPorte, Heather M. (Frontiers in Endocrinology, 2024)
Historically, progesterone has been studied significantly within the context of reproductive biology. However, there is now an abundance of evidence for its role in regions of the central nervous system (CNS) associated with such non-reproductive functions that include cognition and affect. Here, we describe mechanisms of progesterone action that support its brain-protective effects, and focus particularly on the role of neurotrophins (such as brain-derived neurotrophic factor, BDNF), the receptors that are critical for their regulation, and the role of certain microRNA in influencing the brain-protective effects of progesterone. In addition, we describe evidence to support the particular importance of glia in mediating the neuroprotective effects of progesterone.Through this review of these mechanisms and our own prior published work, we offer insight into why the effects of a progestin on brain protection may be dependent on the type of progestin (e.g., progesterone versus the synthetic, medroxyprogesterone acetate) used, and age, and as such, we offer insight into the future clinical implication of progesterone treatment for such disorders that include Alzheimer's disease, stroke, and traumatic brain injury.